2019
DOI: 10.1186/s12888-019-2350-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of problematic smartphone usage and associated mental health outcomes amongst children and young people: a systematic review, meta-analysis and GRADE of the evidence

Abstract: BackgroundOver the past decade, smartphone use has become widespread amongst today’s children and young people (CYP) which parallels increases in poor mental health in this group. Simultaneously, media concern abounds about the existence of ‘smartphone addiction’ or problematic smartphone use. There has been much recent research concerning the prevalence of problematic smartphone use is in children and young people who use smartphones, and how this syndrome relates to mental health outcomes, but this has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
341
5
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(464 citation statements)
references
References 64 publications
24
341
5
16
Order By: Relevance
“…A global review by Sohn and colleagues found that there is a significant association between problematic smartphone use and common mental health disorders [17]. Albeit our results concur with the findings of this review, it should be noted that the review synthesised evidence from Europe, America and Asia and not Africa [17]. Further studies in the sub-Saharan African context are therefore needed to make more meaningful comparisons.…”
Section: Discussionsupporting
confidence: 84%
“…A global review by Sohn and colleagues found that there is a significant association between problematic smartphone use and common mental health disorders [17]. Albeit our results concur with the findings of this review, it should be noted that the review synthesised evidence from Europe, America and Asia and not Africa [17]. Further studies in the sub-Saharan African context are therefore needed to make more meaningful comparisons.…”
Section: Discussionsupporting
confidence: 84%
“…As other researchers claim problematic mobile use is an evolving public health concern that requires greater study to determine the boundary between helpful and harmful technology use [11]. The determination of a risk score can allow in the future the establishment of mobile dependence prevalence studies, as well as the establishment of early detection programs and adequate treatment of this current public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…This symptomatology is assimilated to substances addiction, giving rise to the lack of control of impulses, dependence, craving, anxiety, interferences in daily life, in the dream and / or in the personal relationships, among other symptoms [9]. Nowadays, the problematic use of technologies is considered a social problem, being adolescents and young adults the biggest risk group [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…12 Samantha John et al, in their study revealed that when children are withdrawn from smartphones they were distressed and anxious, depressed, angry and develop sleep disturbances, whereas in this study showed 60% of the study group had the same experience. 13 Nirman Kaur et al, depicts that there is a steep rise in screen time in small age group, children who had screen time <1 hr at 14 months of age started watching screen for >2 hours/ day when they are 30 months of age. In this study 82% of the study groups felt that their children activities are mainly connected with electronic gadgets.…”
Section: Discussionmentioning
confidence: 99%